EFEK KONSENTRASI ZAT PENGEMBAN TERHADAP KETUAAN WARNA PADA PENCELUPAN SERAT POLIESTER DENGAN ZAT WARNA DISPERSI - Agus Taufiq (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
This Research study how far the concentration of carrier agent influence to the dyeing result of of poliester cloth with dyestuff of Resolin Red FB. Dyeing process conducted with Resolin Red FB 200% as a dyestuff and four kinds of carrier agent that is metilnaftalena, difenil, triklorbenzena and ortofenilfenol with concentration of carrier agent, from 2 g / l, 4 g / l, 6 g / l and 8 g / l. Hereinafter conducted by examination of colour leveling to the result of dyeing process. The result show that concentration of carrier agent give an effect to the leveling of colour, that is consentration excelsior yielded the better of colour leveling. This research also get, that triklorbenzena type yield the older colour from orto fenilfenol, metilnaftalena and difenil type, with the optimum concentration reached by 6 g / l.Keyword : dispersion, polyester,carrier agent, levelling of colour